2020
DOI: 10.9734/irjpac/2020/v21i2030278
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Biochar Activated with Phosphoric Acid towards Hexavalent Chromium Removal

Abstract: The biochar derived from the dreadful weed water hyacinth (Eichhornia crassipes) was activated with phosphoric acid was utilized for adsorption of hexavalent chromium (Cr (VI)) from the simulated solution. The characterization (Zeta potential, specific surface area, Scanning Electron Microscope analysis) of biochar was done to study the surface properties of the biochar. The modified biochar (379 m2g-1) recorded 49.80% greater surface area in comparison to the pristine biochar (253 m2g-1). Zeta potential of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…The predominant species observed in this solution is Cr 2 O 7 2− and HCrO 4 − as the pH is 2 [9]. Kalaiarasi et al [37] found that maximum Cr removal (90 %) is removed at pH 2, as lower pH influences biochar surface and promotes Cr adsorption. Similarly, Bedada et al [4] discovered that the Cr removal capacity of the adsorbent reduced by 10.3 % as the pH of the solution rose from 2 to 6.…”
Section: Phmentioning
confidence: 83%
See 2 more Smart Citations
“…The predominant species observed in this solution is Cr 2 O 7 2− and HCrO 4 − as the pH is 2 [9]. Kalaiarasi et al [37] found that maximum Cr removal (90 %) is removed at pH 2, as lower pH influences biochar surface and promotes Cr adsorption. Similarly, Bedada et al [4] discovered that the Cr removal capacity of the adsorbent reduced by 10.3 % as the pH of the solution rose from 2 to 6.…”
Section: Phmentioning
confidence: 83%
“…The pore volume is 0.12 cc g −1 , and the pore radius is 32.82 Å. The pore radius revealed mesopores (2–50 nm) as per the International Union of Pure and Applied Chemistry [31, 32, 37]. The BET study demonstrates that ZJSAB, with its surface area, pore volumes, and pore size, provides multiple active sites for Cr(VI) adsorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The restricted adsorption sites could become saturated after being fully occupied by the adsorbed Pb(II) [ 49 ]. The adsorbent was exhausted and could no longer adsorb excess lead cations available in the solution [ 52 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…For instance, sulfuric acid and nitric acid treatments worked well to enhance the carboxyl and nitro functional groups of biochar [139]. H 3 PO 4 may break down aromatic and aliphatic biomass structures and form phosphate/polyphosphate cross bridges that prevent contraction and shrinkage during the pore-forming process [140]. Phosphate-containing compounds have been extensively employed in recent years to remove poisonous metals from soil and aquatic ecosystems [141].…”
Section: Acid and Alkali Modificationmentioning
confidence: 99%